2017
DOI: 10.21914/anziamj.v58i0.10995
|View full text |Cite
|
Sign up to set email alerts
|

Based on SARIMA-BP hybrid model and SSVM model of international crude oil price prediction research

Abstract: We propose two hybrid prediction models for the international crude oil price: sarima-bp hybrid model; and ssvm model. The sarimabp hybrid model combines seasonality analysis and autoregressive integrated moving average with back propagation neural network model. Contents E144 prediction accuracy, and the single sarima model has lowest prediction accuracy. Thus, the ssvm model displays a better performance in oil price prediction. Further, the ssvm model predicts nymex crude oil's closing price will approach 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Similarly, Shuyu Li et al [18] in 2017 compared ARIMA, GM and ARIMA-GM model with each other, in which it was concluded that ARIMA-GM shows high accuracy. Hua Luo et al [1] in 2017 proposed two hybrid models SARIMA-BP and SSVM. After comparing the two models, SSVM performed better.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Shuyu Li et al [18] in 2017 compared ARIMA, GM and ARIMA-GM model with each other, in which it was concluded that ARIMA-GM shows high accuracy. Hua Luo et al [1] in 2017 proposed two hybrid models SARIMA-BP and SSVM. After comparing the two models, SSVM performed better.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this paper the time series models used for electric load forecasting are SARIMA and ARIMA. Time series analysis is observing the time sequence and then finding its change in trend, forecasting its future [20].Time series analysis technique becomes a very efficient method when we can't find the important factors that leads to data conversions, from many other factors [1].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many fast optimization algorithms can be used to solve it, which greatly reduces the PLOS ONE computational complexity. SVM has strict convexity and infinitely differentiable mathematical characteristics, and introduced efficient unconstrained optimization problems, which attracted many scholars to study SSVM models from different perspectives [23][24][25][26][27][28][29], Some proposed different smoothing functions [23][24][25][26], while others extended them to the prediction field [16,17]. Other applications of SVM and SSVM are introduced in [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad, Abdul [22] used the SARIMA model to predict the crude palm oil and kernel palm production between June 2011 and May 2011 with the study results also showing that SARIMA is the most fitted model compared to other methods. Furthermore, Luo et al [23] deployed SARIMA with a back propagation neural network (SARIMA-BP) hybrid model to forecast the international crude oil price from January 2002 to April 2006.…”
Section: Introductionmentioning
confidence: 99%